Effects of Zinc Treatments on Yield and Some Agronomic Traits of Durum Wheat Cultivars - Hatun BARUT; Tuğba ŞİMŞEK; Sait AYKANAT (Türkiye Tarımsal Araştırmalar Dergisi, 2017)
This study was carried out to determine the effects of zinc applications on the development, yield and yield components of widespread durum wheat cultivars in Çukurova Region. Amanos-97 and Fuatbey-2000 durum wheat cultivarswere used in the research. Field experiments were performed by two different zinc application methods; via soil and via soil+foliage. In both trials, 0, 0.5, 1, 2, 3, and 4 kg Zn da-1pure zinc doses were applied to the soil. 0.4% ZnSO4.7H2O solution was used for foliar zinc applications. As a result of the research, it has been determined that application of zinc via soil and via soil+foliage is not statistically effective on plant height, biological yield, stem yield, harvest index and grain yield of durum wheat. The application of zinc via soil were found statistically significantly effective at 1% level on thousand grains weight, number of spikes per square meter and zinc concentration of the grains. As a result of the research, it has been determined that when basal soil Zn content was0.23-0.24 ppm, application of 1-2 kg da-1of zinc via soil has positive effects on grain zinc concentration, yield and yield components. It has also been determined that soil+foliar application of zinc is more effective on zinc concentration of grains.